An assessment of preventive risk management in hospitals of the north of Iran - mansoore golchoobi; ghahraman mahmoodi alami (فصلنامه ابن سینا, 2018)
Background: Increasing clinical risks has become a public concern among policymakers as well as healthcare providers and authorities. Risk management is a set of continuous and developing processes that can be taken in the hospitals. This research was conducted with the aim of evaluating preventive risk management in northern hospitals in 2016. Materials and methods: This cross-sectional study assesses medical staff (n=550 individuals) in 15 hospitals in the north of Iran in 2016. Cluster sampling was done, and preventive risk management assessment questionnaire was randomly distributed among physicians and nurses. To analyze data in the analytical study, the distribution of the variables values was investigated using the Kolmogorov-Smirnov test, and also the analysis of variance was performed using the F-test. SPSS software was used to analyze data. Results: The average recognition rate (2.47), status of risk management organizing (2.62), the policy and procedures (3.06), education (3.85), risk management position (2.81), and monitoring the analysis, assessment as well as risk control (2.67), have been obtained. According to the scores obtained in the six component areas of risk management, the overall status of risk management in these hospitals was obtained moderate. Conclusion: Results showed that preventive risk management in the hospitals in the north of Iran was moderate, so hospital managers have to allocate the necessary resources for risk management which is a key factor for patient safety and quality improvement.